2019
DOI: 10.1039/c9mt00205g
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(ii) cation binding by proteins

Abstract: Herein, a set of non-homologous proteins (238) that could bind the cobalt(ii) cations was selected from all the available Protein Data Bank structures with Co2+ cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The ionic radius of Co 2+ is 0.76 Å, which is similar to 0.74 Å of Zn 2+ , 0.69 Å for Cu 2+ , and 0.76 Å for Fe 2+ . Additionally, based on the available Protein Data Bank structures with Co 2+ , the study Khrustalev et al ( 2019 ) found that Co 2+ is commonly bound by cation traps. The traps are formed by relatively negatively charged regions of random coil between a β stand and α helix and between two β strands in which His, Asp, and Glu residues are situated.…”
Section: Cobalt Coenzymes and Proteinsmentioning
confidence: 99%
“…The ionic radius of Co 2+ is 0.76 Å, which is similar to 0.74 Å of Zn 2+ , 0.69 Å for Cu 2+ , and 0.76 Å for Fe 2+ . Additionally, based on the available Protein Data Bank structures with Co 2+ , the study Khrustalev et al ( 2019 ) found that Co 2+ is commonly bound by cation traps. The traps are formed by relatively negatively charged regions of random coil between a β stand and α helix and between two β strands in which His, Asp, and Glu residues are situated.…”
Section: Cobalt Coenzymes and Proteinsmentioning
confidence: 99%
“…Conjugative plasmids encode T4SS primases like TraC of RP4 that contain metallopeptidase domains and relaxases like TraI of RP4 that contain magnesium-binding sites. Cobalt(II) can occupy the same binding site as magnesium or manganese to form different coordination bonds and alter the properties of an active centre 57 . Hence, cobalt complexes may target metal-binding T4SS proteins and interfere with their function.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is worthwhile to point out that substituting zinc ions with cobalt ions is a very useful tool to explore the catalytic properties of enzymes (Kobayashi and Shimizu, 1999). Cobalt is an essential cofactor in many cellular functions (Kobayashi and Shimizu, 1999;Heffern et al, 2013;Khrustalev et al, 2019), but it can also restore the activity of many enzymes in the absence of zinc ions and even accelerate enzyme activity (Fukasawa et al, 2011). However, when working with cells, attention should be paid to the ingredients in the media, since it has been reported that e.g., DMEM has a higher content of histidine, which can chelate cobalt ions, compared to RPMI 1640 and DMEM/ F12 mediums, which seems to be a better choice for cobaltrelated studies, in which growing media is required (Torii et al, 2011).…”
Section: Figurementioning
confidence: 99%